If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7y + 1) + -1(-6y + -8) = 2 Reorder the terms: -1(1 + 7y) + -1(-6y + -8) = 2 (1 * -1 + 7y * -1) + -1(-6y + -8) = 2 (-1 + -7y) + -1(-6y + -8) = 2 Reorder the terms: -1 + -7y + -1(-8 + -6y) = 2 -1 + -7y + (-8 * -1 + -6y * -1) = 2 -1 + -7y + (8 + 6y) = 2 Reorder the terms: -1 + 8 + -7y + 6y = 2 Combine like terms: -1 + 8 = 7 7 + -7y + 6y = 2 Combine like terms: -7y + 6y = -1y 7 + -1y = 2 Solving 7 + -1y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1y = 2 + -7 Combine like terms: 7 + -7 = 0 0 + -1y = 2 + -7 -1y = 2 + -7 Combine like terms: 2 + -7 = -5 -1y = -5 Divide each side by '-1'. y = 5 Simplifying y = 5
| 4g+3h=5i | | 5-3.6X=1.3X+8 | | 6(4x-5)=3(8x+6) | | 2x+5y=-12 | | 11x-29= | | x^4-12x^2+32=0 | | 5-3.6X+1.3X+8= | | 11-9x=38-16x | | 2(x+7)=(2x-5) | | 0.34x-4.56=7.89 | | 4+1.6X=2.9X-12 | | (-2xy*2)(3x*2y*4)= | | 73-2x=4x+7 | | w+3w-48=0 | | 2-2x=14-8x | | 0.0625x+2.125=3 | | 375x-10x^2=0 | | w^3+10w-48=0 | | 10x+4=4(2x+1)-x+5 | | w^2+3w-48=0 | | w^2+10w-48=0 | | 68-3x=6x+24 | | 2x+x+x+9=x+2x+12 | | 7b+4=9b-2 | | -x+1+9x=-2+5x+18 | | -29-7x=9x-19 | | 6x+6+x=3+2x-17 | | 7+4x-3=9x+10-6x | | x+x+x+1=x+17 | | y=0.42x+19.26 | | 0.34x-2.71=1.28 | | 5a-3b=6c |